Penerapan Asas Nebis In Idem Dalam Penyelesaian Sengketa Lingkungan Melalui Gugatan Perwakilan Kelompok Class Action - Eriz Syawaldi; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study examines the theoretical basis of the Nebis In Idem principle in civil cases, especially in class actions and how the basis for the Judges' consideration in applying the Nebis In Idem principle in Class Action Decisions, where the method of approach used in this scientific work is normative juridical, namely research that analyzes laws and regulations with literature studies. Using primary source study materials in the form of regulations, while secondary legal materials include books, articles from accredited journals, besides that tertiary legal materials consist of legal dictionaries. This journal begins with a formulation of the meaning of the application of the Nebis In Idem principle. Then describes descriptively the relationship between Article 10 of PERMA No. 1 of 2002 concerning Class Action Procedures with Article 1917 of the Civil Code. It can be concluded that the theoretical basis of this principle is solely to provide legal protection for a person's human rights, so that a person is not tried for the same case and prioritizes legal certainty and does not let the government repeatedly talk about the same event.